2014
DOI: 10.1097/gme.0000000000000201
|View full text |Cite
|
Sign up to set email alerts
|

Icariin prevents ovariectomy-induced bone loss and lowers marrow adipogenesis

Abstract: Early icariin treatment restores marrow adiposity in the estrogen-deficient rat model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 51 publications
1
29
1
Order By: Relevance
“…20) For phytoestrogens, icariin prevented ovariectomy-induced bone loss and lowered marrow adipogenesis, comparabley with estrogen. 19) Also, puerarin increased adipocyte differentiation, 23) Our data was different from all the above. We found that the OVX-induced adipocyte-increase and adiponectinincrease in supernatant was suppressed significantly by intake of puerarin.…”
Section: Fig 2 Microtomographic Histomorphometry Of the Proximal Tibiacontrasting
confidence: 49%
See 1 more Smart Citation
“…20) For phytoestrogens, icariin prevented ovariectomy-induced bone loss and lowered marrow adipogenesis, comparabley with estrogen. 19) Also, puerarin increased adipocyte differentiation, 23) Our data was different from all the above. We found that the OVX-induced adipocyte-increase and adiponectinincrease in supernatant was suppressed significantly by intake of puerarin.…”
Section: Fig 2 Microtomographic Histomorphometry Of the Proximal Tibiacontrasting
confidence: 49%
“…19) A reciprocal association between osteoblasts and adipocytes deriving from bone marrow stromal cells prompted us to explore the effect of puerarin on adipogenesis at the same time. Unfortunately, our data indicated that the reciprocal changes in bone and adiposity were not directly coupled with one another.…”
Section: Fig 2 Microtomographic Histomorphometry Of the Proximal Tibiamentioning
confidence: 99%
“…Furthermore, biomechanics allow us to identify the biological effects of bone under force or stress [23]. Previous studies have proved that although low bone mass in osteoporotic bones is a major risk factor for the occurrence of a fracture, the presence of adequate trabecular microstructure can preserve the biomechanical properties of the bone [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ICA can improve bone mineral density (BMD) and bone strength in ovariectomized rats [20]. Moreover, Li et al reported that ICA prevented ovariectomyinduced bone loss and lowered marrow adipogenesis [21]. Meanwhile our previous study demonstrated that ICA might have a beneficial effect on the BMSCs of patients with steroidassociated osteonecrosis by demethylation of the adenosine triphosphate-binding cassette (ABC) B1-promoter [14].…”
Section: Introductionmentioning
confidence: 99%